The relationship between accelerometer-based physical activity, sedentary behavior, and seven common geriatric syndromes: a two-sample Mendelian randomization study - Jiping Chen; Yanyu Lu; JiaWei Yao; Xianliang Zhang; Yang Pan (Frontiers Media S.A., 2024)
IntroductionTo investigate the causal associations between accelerometer-based physical activity (PA), sedentary behavior (SB), and seven common geriatric syndromes (GSs) (frailty, falls, delirium, urinary incontinence, dysphagia, hearing loss, and visual impairment) by Mendelian randomization (MR) analysis.MethodsInstrumental variables from a genome-wide association study were used for MR analysis. The exposure factors were three PA phenotypes (average acceleration, overall activity, and moderate-intensity activity) and one SB phenotype (SB). The outcome variables were seven common GSs. The inverse variance weighted (IVW) method was utilized for the primary MR analysis. Additionally, sensitivity, pleiotropy, and heterogeneity analyses were subsequently conducted to assess the robustness of the present study's findings.ResultsAccording to the primary MR results obtained using the IVW method, genetically predicted PA (average acceleration) decreased the risk of two GSs (frailty, p = 0.01; dysphagia, p = 0.03). Similarly, overall activity decreased the risk of two GSs (frailty, p = 0.01; delirium, p = 0.03), and moderate-intensity activity reduced the risk of three GSs (urinary incontinence, p = 0.04; hearing loss, p = 0.02; visual impairment, p = 0.01). Furthermore, SB was causally correlated with a greater risk for three GSs (frailty, p = 0.03; fall, p = 0.01; dysphagia, p = 0.04).ConclusionThis study provided evidence that accelerometer-based PA may be causally associated with a lower risk of GSs, while SB may increase the risk of GSs.